The Legal Nature of Artificial Intelligence Hardware and Software (Smart Robots). - Ghazaleh, Shereen Abu; Alabady, Hassan Sami; Al-Khalaileh, Lana (Journal of Human Security (Librello Publishing House), 2024)
Smart robots represent a pivotal application within the domain of artificial intelligence, embodying automated systems imbued with specialized software facilitating either predetermined actions akin to conventional robots or independent decisionmaking capabilities akin to autonomous entities. However, an inherent dilemma emerges regarding accountability when such robots cause harm. This prompts inquiry into the allocation of responsibility and the applicability of established legal frameworks to contemporary circumstances. Furthermore, consideration is given to the prospect of endowing these entities, particularly autonomous robots, with legal personhood, as exemplified by the concept of general rules for robots. Delving into the European Parliament's stance on this matter elucidates current perspectives and anticipates potential future trajectories concerning the attribution of legal personality to autonomous robots. Consequently, this qualitative investigation endeavours to elucidate the legal status of Artificial Intelligence (AI) hardware and software, with a particular focus on intelligent robots. Employing a normative research methodology, the study aims to discern that the unique nature of robots necessitates bespoke legislative measures. Ultimately, the findings of this study serve as instrumental insights for regulatory bodies and lawmakers, facilitating the development of judicious and targeted platforms rooted in AI technology.